Costs and quality of life in multiple sclerosis patients with spasticity. (18th May 2013) - Svensson, J.; Borg, S.; Nilsson, P.
<x xml:space="preserve">Abstract</x> Background The resource use and health‐related quality of life (HRQoL) of patients with multiple sclerosis (MS) spasticity are not well known. The purpose of this study was to obtain estimates of resource utilization, costs, and HRQoL, for patients with different levels of MS spasticity in southern Sweden. Material and methods Cross‐sectional data on spasticity severity (using a Numerical Rating Scale, NRS), resource use and HRQoL (using EQ‐5D) were collected using a patient questionnaire and chart review. Patients were recruited through a clinic in southern Sweden. The study reviews direct medical, direct non‐medical and indirect costs. Results Total costs were estimated to €114, 293 per patient and year. Direct medical costs (€7898) accounted for 7% of total costs. Direct non‐medical costs (€68, 509) accounted for 60% of total costs. Total costs increased with severity of spasticity: for patients with severe spasticity, the total cost was 2.4 times greater than those for patients with mild spasticity. HRQoL decreased as spasticity increases. Conclusion The results of this study show that MS spasticity is associated with a substantial burden on society in terms of costs and HRQoL.